(untitled) (Malaysian Journal of Learning and Instruction, 2004)
Malay adolescents’ perceptions of parenting styles are assessed via Maternal and Paternal Parenting Style questionnaire. Subjects are Malay boys (n= 146) and girls (n= 284) in secondary schools. Both parents are perceived as being low in demandingness but high in responsiveness. Mothers are being rated lower in demandingness and higher in responsiveness compared to fathers. In terms of parenting style, both parents are perceived as being permissive. In addition, a high percentage of parents are reported as being uncertain in their parenting practices.